Índice de área foliar e produtividade do tomate sob condições de ambiente protegido - Reis, Ligia S.; de Azevedo, Carlos A. V.; Albuquerque, Abel W.; Junior, Josué F. S. [UNESP] (FapUNIFESP (SciELO), 2013)
The tomato cultivation in the greenhouse has been expanded in the last years, mainly, in the South and Southeast regions of Brazil, whose purpose is to improve the productivity and the quality of the agricultural products, offering regularity in the production. The present study aimed to determine, along the crop cycle, the relationship between the leaf area index and the productivity, and at the end of the cycle, the components of production of the tomato in the greenhouse. The models were generated through polynomial equations of 1st and 2nd order, having as independent variable the number of days after the transplanting. It was verified that it is possible to determine, in the greenhouse, through mathematical models, the leaf area index of the tomato crop considering the days after the transplanting. Basing on values of leaf area index, the productivity of the crop and the period of the maximum productivity can be determined, aiding the farmers to determine the best sowing and transplanting time of the tomato crop.
Leaf area index and productivity of tomatoes under greenhouse conditions
Keywords: Crop management; Lycopersicon esculentum; Models; Weather variables